2019
DOI: 10.1177/1947603519852415
|View full text |Cite
|
Sign up to set email alerts
|

First Clinical Application of Polyurethane Meniscal Scaffolds with Mesenchymal Stem Cells and Assessment of Cartilage Quality with T2 Mapping at 12 Months

Abstract: Background Complex meniscal lesions often require meniscectomy with favorable results in the short term but a high risk of early osteoarthritis subsequently. Partial meniscectomy treated with meniscal substitutes may delay articular cartilage degeneration. Purpose To evaluate the status of articular cartilage by T2 mapping after meniscal substitution with polyurethane scaffolds enriched with mesenchymal stem cells (MSC) and comparison with acellular scaffolds at 12 months. Methods Seventeen patients (18-50 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…In Monllau's study, PU scaffold resorption and the incomplete in-growth of new meniscus-like tissue was observed [ 267 ]. Recently, the first clinical report of PU meniscal scaffolds with MSCs was published [ 268 ]. Seventeen patients (18–50 years old) with past meniscectomies were separated into two groups: acellular PU scaffold and MSC-enriched PU scaffold.…”
Section: Biodegradable Thermoplastic Polyurethane Scaffolds For Tissu...mentioning
confidence: 99%
“…In Monllau's study, PU scaffold resorption and the incomplete in-growth of new meniscus-like tissue was observed [ 267 ]. Recently, the first clinical report of PU meniscal scaffolds with MSCs was published [ 268 ]. Seventeen patients (18–50 years old) with past meniscectomies were separated into two groups: acellular PU scaffold and MSC-enriched PU scaffold.…”
Section: Biodegradable Thermoplastic Polyurethane Scaffolds For Tissu...mentioning
confidence: 99%
“…In fact, polyurethane-based materials are already being tested in clinical trials. 49,50 3D bioprinting technology allows us to fabricate b-TPUe scaffolds with the desired thickness of fiber and pore size, biomimicking the tissue microstructure, and thus ameliorating the integration of the scaffold within the specific location. The porosity and interconnectivity of the scaffold plays a significant role in nutrient supply, gas diffusion and metabolic waste removal.…”
Section: Discussionmentioning
confidence: 99%
“…However, this advantage of MSC loading disappeared after 12 weeks ( Koch et al, 2018 ). It has also been reported that MSC-seeded PU scaffolds exhibit little additional clinical benefit in the protection of articular cartilage ( Olivos-Meza et al, 2019 ).…”
Section: Polymers For Meniscal Tissue Engineering Applicationsmentioning
confidence: 99%